2020
DOI: 10.1111/ijac.13539
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of a SiC/SiC ceramic composite with an ytterbium‐disilicate environmental barrier coating at elevated temperature*

Abstract: Tension‐tension fatigue performance of a SiC/SiC composite with an ytterbium‐disilicate environmental barrier coating (EBC) was investigated at 1200°C in air and steam. The composite is reinforced with Hi‐Nicalon™ SiC fibers and has a melt‐infiltrated matrix processed by chemical vapor infiltration of SiC with subsequent infiltration with SiC particulate slurry and molten silicon. The EBC consists of a Si bond coat and an Yb2Si2O7 top coat applied via air plasma spraying. Tensile properties were evaluated at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The largest deviation from the nominal test temperature was ±1°C in air and ±2°C in steam. A detailed description of the experimental set‐up is given elsewhere 34,41–43 . All tests were conducted at 1200°C.…”
Section: Materials and Experimental Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest deviation from the nominal test temperature was ±1°C in air and ±2°C in steam. A detailed description of the experimental set‐up is given elsewhere 34,41–43 . All tests were conducted at 1200°C.…”
Section: Materials and Experimental Arrangementsmentioning
confidence: 99%
“…A detailed description of the experimental set-up is given elsewhere. 34,[41][42][43] All tests were conducted at 1200 • C. In all tests, a specimen was heated to test temperature at 1 • C/s and held at that temperature for additional 45 min prior to testing.…”
Section: Materials and Experimental Arrangementsmentioning
confidence: 99%
“…Ruggles-Wrenn et al [69] studied the fatigue behaviour of the ytterbium disilicate environmental barrier coating on a SiC/SiC ceramic composite at elevated temperatures. The tension-tension fatigue property of the EBC-containing composite was examined in both air and steam at 1200 • C. It was observed that in the air, the EBC system shows a lower fatigue limit and a shorter cyclic life than the uncoated CMC.…”
Section: Recession Of Environmental Barrier Coatingsmentioning
confidence: 99%
“…In addition to water-vapor-induced oxidation and recession, EBCs need to be resilient against thermal and thermo-mechanical stress/strain [11][12][13][14][15][16], calcium-magnesiumaluminosilicate (CMAS) deposits [17][18][19][20][21][22], foreign object damage (FOD) [23,24], and solid particle erosion (SPE) [25][26][27]. While many of the aforementioned degradation modes have been investigated, there is still a gap in the characterization and fundamental understanding of the SPE behavior of EBCs.…”
Section: Introductionmentioning
confidence: 99%